2021
DOI: 10.3389/fphys.2021.659291
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Vasodilation Mediated by G Protein-Coupled Estrogen Receptor (GPER) in Hypertensive Rats

Abstract: BackgroundThe protective effect of estrogen on the vasculature cannot be explained only by its action through the receptors ERα and ERβ. G protein-coupled estrogen receptors (GPER)—which are widely distributed throughout the cardiovascular system—may also be involved in this response. However, little is known about GPER actions in hypertension. Therefore, in this study we evaluated the vascular response mediated by GPER using a specific agonist, G-1, in spontaneously hypertensive rats (SHR). We hypothesized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…GPER1 is widely distributed in the cardiovascular system and exerts protective effects on the vasculature ( 112 ). GPER1 decreases blood pressure, promotes vasodilation, and reduces the proliferation and migration of VSMCs ( 223 ).…”
Section: Ers In the Manifestation Of Diseasesmentioning
confidence: 99%
“…GPER1 is widely distributed in the cardiovascular system and exerts protective effects on the vasculature ( 112 ). GPER1 decreases blood pressure, promotes vasodilation, and reduces the proliferation and migration of VSMCs ( 223 ).…”
Section: Ers In the Manifestation Of Diseasesmentioning
confidence: 99%
“…The following supporting information can be downloaded at: . References [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ] are cited in Supplementary Materials.…”
mentioning
confidence: 99%
“…Animal studies addressing EDH-mediated relaxations revealed a well-defined production of cyclooxygenases and NO synthase inhibitors that are coupled with hyperpolarization of VSMCs located in the proximity of these molecular reactions. Some experimental studies have established the heterogeneous nature of EDH factors by reporting the specific characteristics relating to the different species and vascular beds of concern [ 53 , 54 , 55 ]. Greater production of epoxyeicosatrienoic acids, which constitute the fundamental metabolites of the arachidonic P450 epoxygenase sequential reactions were noted [ 56 , 57 , 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%